A study on assessment of knowledge and acceptance of human papilloma virus vaccination among the parents of adolescent girls of North Karnataka - Badakali, Meenakshi A.; Rangappa, Manjula (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Infection with the human papillomavirus (HPV) is the most common sexually transmitted infection (STI). In India, cervical cancer is the second most common women’s cancer in the country. Approximately 80% of cancers caused by HPV can be prevented by administering the HPV vaccine. The current study was taken up to identify the factors influencing HPV knowledge and vaccine acceptance in the parents of adolescent girls. Methods: A school based cross sectional study design was used. A total of 240 parents participated in the present study. A predesigned questionnaire was used for obtaining their knowledge and acceptance of HPV vaccine for their children. Statistical analysis was done using SPSS software 19.0. Results: In the present study only 49.6% of them had acceptance about HPV vaccinations for their daughters. 78.3% of them felt that vaccine could prevent infection and could be safe. 54.6% knew about cervical cancer. 34.2% of them felt that the vaccine is painful and may have side effects. 50.8% of them thought that their children are too young to get cervical cancer. 74.6% felt the protection from the vaccine is short lived. Conclusions: Despite the high efficacy rate of HPV vaccines, adolescent vaccine coverage is very poor due to lack of awareness of its efficacy and safety among parents of adolescent children. Concerted efforts are needed by public and private healthcare sectors to increase the awareness of the disease and increase HPV vaccine coverage.